Microbiome-metabolome integration reveals fermentation-driven divergence in bioactive compound profiles of Cardamine violifolia leaf pickles - Jue Gong; Shen Rao; Xiaomeng Liu; Shuiyuan Cheng; Xin Cong; Dingxiang Zhu (Current Research in Food Science, 2025)
Cardamine violifolia is an emerging cruciferous vegetable rich in nutrients and bioactive components. This study investigated the microbial community and metabolite profiles in C. violifolia leaf pickles prepared using three fermentation methods: natural fermentation (NF), inoculation with Lactiplantibacillus plantarum (LP), and inoculation with Leuconostoc mesenteroides (LM). Results revealed that fermentation significantly altered the microbial composition, with Firmicutes becoming the dominant phylum. Lactococcus and Weissella were predominant in both the NF and LM groups, while Lactiplantibacillus dominated in the LP group. Metabolomic analysis identified 865 metabolites in total, with amino acids, lipids, and alkaloids representing the most abundant classes. Fermentation enhanced the production of bioactive compounds (e.g., alkaloids, phenolic acid, flavonoids), particularly in the LP group. Correlation analysis indicated a strong relationship between specific microorganisms and active metabolites. These findings suggest that fermentation not only improved the edible and nutritional value of C. violifolia leaf pickles but also enhanced their potential health benefits.